2023
DOI: 10.3389/fpubh.2023.1081360
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting psychological health and career choice among medical students in eastern and western region of China after COVID-19 pandemic

Abstract: IntroductionTo unearth superior countermeasures that improve psychological health and upgrade the quality of employment for medical students in China in post-epidemic era, this study was designed to determine the possible factors affecting psychological status and future career choice of this population.MethodsA cross-sectional observational study was carried out. Depression Anxiety Stress Scale-21 (DASS-21) and Insomnia Severity Index (ISI) were applied to measure psychological state. Chi-square and logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Our study found that majority of the students came from lower income families. Lower family income can be attributed to another major determinant for depression and insomnia as it can lead to financial hardship, limited access to healthcare, difficult living situations, emotional distress and poor nutrition 83 . Different people have different biological cycles and prefer the morning or evening for work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that majority of the students came from lower income families. Lower family income can be attributed to another major determinant for depression and insomnia as it can lead to financial hardship, limited access to healthcare, difficult living situations, emotional distress and poor nutrition 83 . Different people have different biological cycles and prefer the morning or evening for work.…”
Section: Discussionmentioning
confidence: 99%
“…Lower family income can be attributed to another major determinant for depression and insomnia as it can lead to financial hardship, limited access to healthcare, difficult living situations, emotional distress and poor nutrition. 83 Different people have different biological cycles and prefer the morning or evening for work. The MT always prefers the morning hour and the ET prefers the evening hour to accomplish their work.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 140 million patients worldwide choose to wear CL instead of frame glasses each year because of their advantages, such as aesthetics, ease of movement, and low cost ( 1 ). In the context of the increasingly widespread use of electronic products, myopia in adolescents has shown a high incidence trend in recent years ( 2 ). According to a survey by the National Health Commission, the overall myopia rate among children and adolescents in China is 52.7%, with 14.3% for 6-year-old children, 35.6% for primary school students, 71.1% for middle school students, and 80.5% for high school students, respectively ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…No início da pandemia da COVID-19 as faculdades e universidades foram fechadas e o ensino remoto foi adotado em grande escala, os estudantes universitários em quarentena não apenas precisaram superar o incômodo do distanciamento social, mas também tiveram que lidar com diversas mudanças e se adaptarem às novas formas de aprender 9,10 . Durante a pandemia, verificou-se uma alta prevalência de problemas relacionados à saúde mental, principalmente em acadêmicos dos cursos de ciências da saúde, que sofreram mais com ansiedade, depressão e estresse 9,11,12 .…”
Section: Introductionunclassified